The ethics of Aquinas - Pope, Stephen J.; (1955-...) (U.S.A, 2002)
In this comprehensive anthology, twenty-seven outstanding scholars from North America and Europe address every major aspect of Thomas Aquinas' understanding of morality and comment on his remarkable legacy. The opening chapters introduce readers to the sources, methods, and major themes of Aquinas' ethics. The second part of the book provides an extended discussion of ideas in the Second Part of the Summa Theologiae, in which contributors present cogent interpretations of the structure, major arguments, and themes of each of the treatises. The third and final part examines the legacy of Thomistic ethics for the twentieth century and today.
Keywords: Thomas, -- Aquinas, Saint, -- 1225? -1274 -- Summa theologica -- Part 2